2019
DOI: 10.1111/jsr.12915
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota perturbation is associated with acute sleep disturbance among rectal cancer patients

Abstract: Summary Cancer treatment‐associated gut microbial perturbation/dysbiosis has been implicated in the pathobiology of sleep disturbance; however, evidence is scarce. Eighteen newly diagnosed rectal cancer patients (ages 52–81 years; 10 males) completed a sleep disturbance questionnaire and provided stool samples for 16s RNA gene sequencing during chemo‐radiotherapy. Descriptive statistics, Wilcoxon test and regression analyses were computed. Regression analyses showed the Shannon's diversity index to be a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Because of the small sample sizes, our results are exploratory in nature and should be interpreted with caution. Nonetheless, this proof-of-concept pilot study builds on prior evidence from our group that CRT-induced comorbidities/symptoms may be associated with gut-microbial dysbiosis (Gonzalez-Mercado et al, 2020; Gonzalez-Mercado et al, 2019). In the present study, we compared the severity of fatigue, sleep disturbance, and depression scores before and at the end of CRT between participants who developed co-occurring symptoms by the end of CRT ( n = 24) and those who developed no symptom ( n = 7).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Because of the small sample sizes, our results are exploratory in nature and should be interpreted with caution. Nonetheless, this proof-of-concept pilot study builds on prior evidence from our group that CRT-induced comorbidities/symptoms may be associated with gut-microbial dysbiosis (Gonzalez-Mercado et al, 2020; Gonzalez-Mercado et al, 2019). In the present study, we compared the severity of fatigue, sleep disturbance, and depression scores before and at the end of CRT between participants who developed co-occurring symptoms by the end of CRT ( n = 24) and those who developed no symptom ( n = 7).…”
Section: Discussionmentioning
confidence: 89%
“…A major gap in the prevention and management of CRT-associated co-occurring symptoms is that there are no known targets for effective interventions. Previous research suggests that gut microbial perturbation/dysbiosis, a disruption in the balance, diversity, and function of symbiotic intestinal microbial communities (Perez et al, 2020) may be an important correlate of the symptom experience among patients with pelvic cancer undergoing treatments, perhaps mediated by the gut–brain axis (Bajic et al, 2018; Gonzalez-Mercado et al, 2019, 2020; Jordan et al, 2018). We previously demonstrated that gut microbial dysbiosis in RC patients was characterized by significantly lower alpha (within-sample) diversity at the end of CRT compared to before treatment using both Shannon diversity (community diversity) and the observed operational taxonomic units (OTUs [community richness]) for the RC sample as a whole ( p < 0.05; Gonzalez-Mercado et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence by our group (González-Mercado et al 2019;González-Mercado, Pérez-Santiago, et al, 2020) and others (Wang et al, 2015) suggests that gut microbial dysbiosis may play an important role in the pathogenesis of common symptoms including depressive symptoms, sleep disturbance, and fatigue. In this study, we observed no significant differences in microbial alpha diversity between rectal cancer patients with high as compared to low co-occurring symptoms before CRT.…”
Section: Low Bacterial Diversity Indices Do Not Associate With Co-occurring Symptomsmentioning
confidence: 97%
“…Changes in gut microbiota composition induced by factors such as cancer or its treatment have been suggested to be associated or potentially causal of dysbiosis (a disruption in the balance, diversity, and function of symbiotic intestinal microbial communities) [ 2 , 13 ] in depression and other comorbidities/symptoms [ 2 , 11 , 14 16 ]. We recently reported reduced alpha diversity (Shannon Diversity and Observed Operational Taxonomic Units (OTUs)) in rectal cancer patients in the middle and at the end of CRT compared to before CRT, suggesting that CRT is associated with alterations in gut microbiota composition [ 15 ].…”
Section: Introductionmentioning
confidence: 99%